2017
DOI: 10.1002/1878-0261.12044
|View full text |Cite|
|
Sign up to set email alerts
|

Functional KRAS mutations and a potential role for PI3K/AKT activation in Wilms tumors

Abstract: Wilms tumor (WT) is the most common renal neoplasm of childhood and affects 1 in 10 000 children aged less than 15 years. These embryonal tumors are thought to arise from primitive nephrogenic rests that derive from the metanephric mesenchyme during kidney development and are characterized partly by increased Wnt/β‐catenin signaling. We previously showed that coordinate activation of Ras and β‐catenin accelerates the growth and metastatic progression of a murine WT model. Here, we show that activating KRAS mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…We have previously shown that when grafted orthotopically these cells grow into tumors, metastasize to the lung, and recapitulate many of the features of human WT. 33 Compared to placebo treated control, four weeks of pyrvinium treatment significantly reduced the size of the primary tumors (Figure 1). It also profoundly reduced the number and size of the lung metastases seen at necropsy (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…We have previously shown that when grafted orthotopically these cells grow into tumors, metastasize to the lung, and recapitulate many of the features of human WT. 33 Compared to placebo treated control, four weeks of pyrvinium treatment significantly reduced the size of the primary tumors (Figure 1). It also profoundly reduced the number and size of the lung metastases seen at necropsy (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
“…To test whether pharmacologic inhibition of β-catenin transcription can inhibit growth and metastatic disease progression, we grafted murine renal epithelial cells with activating mutations of both Kras and β-catenin (Kras/Catnb cells) under the renal capsule of nude mice as previously described 33 . We have previously shown that when grafted orthotopically these cells grow into tumors, metastasize to the lung, and recapitulate many of the features of human WT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS activation can trigger several important signaling pathways, such as the PI3K/ AKT and MAPK/ERK pathways, most of which regulate cell proliferation and invasion [17][18][19][20]. Therefore, we investigated the possibility that miR-216b regulates those pathways by targeting KRAS.…”
Section: Mir-216b Inhibits the Akt And Erks Pathwaysmentioning
confidence: 99%
“…The following disclosure has been added to the original article (Polosukhina et al ., ). Dr. Arteaga was on a Novartis Advisory Board at the time of publication, but the Board service was unrelated to this study.…”
mentioning
confidence: 97%